Sad and violent but I enjoy it: Children's engagement with dark tourism as an educational tool. (October 2019) - Israfilova, Firangiz; Khoo-Lattimore, Catheryn
This article aims to study the educational importance of dark tourism suppliers, with a particular focus on children's experiences after their exposure to dark sites. The answers of 25 young visitors from two different secondary schools to a genocide site revealed four major impacts of the educational trip on them. From an educational curriculum framework, the respondents' experiences are categorised into knowledge expansion, character building, emotional challenges and edutainment factors. The findings of the research indicate that children's visit to a thanatological attraction fills their knowledge gap and motivates them to study history, and forms a character of patriotism encouraged by their observations at the site. The emotional and entertainment features of the trip are also revealed in this paper.